IMPLEMENTATION OF CANVA IN SCIENCE STUDY AT UJONG PULO CUTSTATE ELEMENTARY SCHOOL ININDUSTRY REVOLUTION ERA 4.0 - Heri Salmita; Akmaluddin; Siti Mayang Sari; Musdiani (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
In the application of Canva to science subjects in elementary schools and during the 4.0 industrial revolution, this was very continuous or related because during the 4.0 industrial reform era, technology was more prioritized. To achieve a science learning goal in elementary school, we need to use technology in the form of the Canva application in making learning media. In science learning, the Canva application is referred to as the parent or auxiliary tool for those in grade 5, such as those relating to humans, animals and inanimate objects. are around our environment. This data is obtained through qualitative research where data is obtained by direct observation or the opinions of several people who play an important role in educational institutions. And we can use the results of this research as a basis or example which will refer to what the benefits of applying Canva to science subjects in elementary schools during the industrial reform 4.0 period